NEW STUDENT REGISTRATION INFORMATION SYSTEM AT THE WAISUMAR STATE ELEMENTARY SCHOOL MODEL SCHOOL - Hendrikus U Ngaru Galar; Adelbertus U Janga; Felysitas Ema Ose Sanga (JTH: Journal of Technology and Health, 2023)
Registration carried out by the system automatically provides announcements of registration results carried out online. Prospective new students can find out announcements easily using the internet. The implementation of online admissions for new students is considered to have its own advantages and benefits. Apart from being more efficient, online acceptance of new students is more transparent and open. This includes facilitating monitoring both by students or parents and the community as well as by departments and related parties. The method used in this research is a data collection technique where there are observations, interviews and literature studies. This new student admissions information system was built using the PHP programming language and utilizes the MySQL database as the database server. It is hoped that this research can help prospective new students and new student admissions officers in the process of registering new students at the Waisumar State Elementary School.